2015
DOI: 10.5897/ijbc2014.0787
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and community composition of small mammals in different habitats in Hugumburda forest, northern Ethiopia

Abstract: Tropical forest ecosystems harbor several species of small mammals. Diversity and abundance of small mammals in these forests reflect the quality and diversity of the ecosystems. The current study was carried out to assess abundance and species composition of small mammals (rodents and shrews) in three habitat types (Pterolobium, Juniperus and Cadia habitats) in Hugumburda forest, a dry afromontane forest in the Tigray region of North Ethiopia. The habitat types were selected based on the floristic composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…During the present study, we recorded the presence of two Ethiopian endemic rodents—Awash Multimammate Mouse Mastomys awashensis (Lavrenchenko et al, 1998) and Ethiopian White‐footed Mouse Stenocephalemys albipes (Rüppell, 1842; Figure 1) in KSNP. The morphometric and cranio‐dental measurements (Table 1) are well within the range of the species (Mengistu et al, 2015; Meseret & Solomon, 2014) and the skull morphology (Figure 2) also confirms for better identification. We captured a total of 17 individuals comprise different age groups of Mastomys awashensis and 55 individuals of Stenocephalemys albipes from all habitat types except the grass land.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…During the present study, we recorded the presence of two Ethiopian endemic rodents—Awash Multimammate Mouse Mastomys awashensis (Lavrenchenko et al, 1998) and Ethiopian White‐footed Mouse Stenocephalemys albipes (Rüppell, 1842; Figure 1) in KSNP. The morphometric and cranio‐dental measurements (Table 1) are well within the range of the species (Mengistu et al, 2015; Meseret & Solomon, 2014) and the skull morphology (Figure 2) also confirms for better identification. We captured a total of 17 individuals comprise different age groups of Mastomys awashensis and 55 individuals of Stenocephalemys albipes from all habitat types except the grass land.…”
Section: Resultssupporting
confidence: 67%
“…In Ethiopia, a total of 84 species of rodents were recorded, of which 21% are endemic (Alembrhan & Srinivasulu, 2019; Bryja et al, 2019; Lavrenchenko et al, 2007; Yalden & Largen, 1992). Most endemic rodents of Ethiopia were recorded from the high altitudinal ranges (Afework, 1996; Bryja et al, 2019; Lavrenchenko et al, 2007; Yalden & Largen, 1992), leading to confinement of extensive surveys of rodents to the highlands (Demeke & Afework, 2014; Gezahegn et al, 2016; Mengistu et al, 2015; Mohammed et al, 2010). Investigations of rodent diversity in lowland areas of Ethiopia were not conducted; thus, the rodent communities in such areas, including Kafta‐Sheraro National Park (KSNP), are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Such novel studies should focus on species that are sensitive to disturbances or that could help better evaluate the level of habitat integrity. In this context, terrestrial small mammals, which ecological importance has already been demonstrated (Adam et al, 2015;Bantihun & Bekele, 2015), are eligible.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore difficult to appreciate the terrestrial small mammal communities in the TNP in terms of diversity and abundance. However, it is recognised that terrestrial small mammals form an important component of tropical natural environments (Adam et al, 2015;Bantihun & Bekele, 2015). Terrestrial small mammals play an important ecological role.…”
Section: Introductionmentioning
confidence: 99%